Facilitators and Barriers to Hiv Pre-Exposure Prophylaxis Adherence and Retention Among Young Men Who have Sex With Men: A Meta-Ethnographic Scoping Review. - Tuan, Le Anh; Pham, Loc Quang; Khuyen, Tong Thi; Hao, Bui Minh; Hoa, Nguyen Thi Phuong; Vu, Kim-Duy; Lien, Tran Hoang My; Duyen, Pham Thi Thanh; Phan, Hai Thanh; Giang, Le Minh; Bartels, Sophia M.; Rutstein, Sarah E. (AIDS & Behavior, 2025)
Retention and adherence to daily oral pre-exposure prophylaxis (PrEP) are critical for effective HIV prevention; however, YMSM exhibit lower rates of both compared to other populations. This is important because young men who have sex with men (YMSM) are at higher risk for HIV, and understanding their challenges can help create better support and interventions. This scoping review synthesizes evidence on the facilitators and barriers to HIV PrEP retention and adherence among YMSM, focusing on individuals aged 10 to 29 years. The review adheres to PRISMA-ScR and eMERGe guidelines, examining 14 studies involving 3,178 participants. It emphasizes the complex interactions of individual, interpersonal, community, and societal factors influencing PrEP adherence and retention. Key facilitators include psychological strategies, supportive health systems, and supportive social networks. Conversely, significant barriers encompass financial burdens, interpersonal stigma, and behavioral factors. The review highlights the critical role of tailored, multi-level interventions and the need for healthcare provider training in youth-specific approaches to care. This work contributes to a nuanced understanding of PrEP retention among YMSM, offering insights crucial for designing effective public health strategies to enhance prevention-effective PrEP utilization in this high-risk population.